Correlation of cation distribution with the hyperfine and magnetic behaviour of Ni0.3Zn0.4Co0.2Cu0.1Fe2O4 nanoparticles and their microwave absorption properties when encapsulated in multi-walled carbon nanotubes. (16th January 2017) - Dalal, Madhumita; Mallick, Ayan; Greneche, Jean-Marc; Das, Dipankar; Chakrabarti, Pabitra K
Abstract: Nanocrystalline samples of Ni0.3 Zn0.4 Co0.2 Cu0.1 Fe2 O4 (NZCCF) are prepared by a simple co-precipitation method. To obtain nanoparticles of different sizes, the as prepared sample is annealed at 400, 600, 800 and 1000 °C. Nanoparticles of the sample annealed at 600 °C are encapsulated in multi-walled carbon nanotubes (MWCNT). To confirm the crystallographic phase, x-ray diffraction (XRD) patterns are analyzed by the Rietveld method and cation distribution in A- and B-sites is estimated from the analysis. Occupancy of Zn 2+ ions in A-site and that of Fe 3+ ions in B-site increase with the increase of annealing temperature ( T A ) and lattice parameters lie within 8.365–8.398 Å. Morphology of the encapsulated sample is examined by taking micrographs in high resolution transmission electron microscope (HRTEM). Hyperfine behaviour of the prepared samples is studied by analyzing Mössbauer spectra recorded at room temperature (RT) and 77 K. Average values of isomer shift (IS) are found to decrease with the increase of crystallite size. Static and dynamic magnetic hysteresis loops are recorded to analyze the magnetic properties of the sample. Maximum saturation magnetization of 75 emu g −1 is obtained for the sample of NZCCF annealed at 800 °C with crystallite size of 48 nm. Microwave absorption capability of the encapsulated sample is measured by recording the reflection loss in X and K u bands of microwave region of frequency. Maximum value of reflection loss is −25.71 dB observed at 15.24 GHz for a sample layer thickness of 1 mm. Moreover, the reflection loss is less than −10 dB for the entire range of observation (8–18 GHz) which shows that MWCNT encapsulated NZCCF could be considered as a potential candidate for applications in microwave devices.